Lifetime risk of stroke in the general male population. (10th March 2020) - Rusek, Linnéa; Persson, Carina U.; Svärdsudd, Kurt; Blomstrand, Ann; Blomstrand, Christian; Welin, Lennart; Caidahl, Kenneth; Hansson, Per‐Olof
Abstract : Objectives: Most previous studies of incidence rates of stroke are from register studies, while data from prospective cohort studies are limited. The aim of the present study was to describe hazard rates, prevalence and cumulative proportion free from stroke during a lifelong follow‐up of a representative sample of middle‐aged men sampled from the general population. Methods: A population‐based sample of 855 men, all born in 1913, was investigated at 50 years of age and followed up with repeated medical examinations at age 54, 60, 67, 75 and 80. Data from hospital records and the Cause of Death Register were collected, and all stroke events during 48 years of follow‐up were registered. Medical records were scrutinized in order to confirm and validate the stroke diagnoses. Results: One man was excluded because of stroke prior to baseline, while 176 of the remaining 854 men (20.7%) suffered a first‐ever stroke during follow‐up. The total 5‐year stroke risk (hazard rate) increased with age, from 3.54 (95% CI: 0‐7.55) per 1000 persons at risk at age 50 years, to 119.05 (95% CI: 45.39‐192.70) at age 90 years. The stroke prevalence peaked at age 80 and older, with about 120 cases per 1000 years of observation. The survival rate (cumulative proportion free from stroke) at age 98 was 50.0%. Conclusion: One out of five men in this population sample suffered a stroke of any type during follow‐up from 50 to 98 years of age and the cumulative incidence was close to 50%.